METHODOLOGY OF FACTOR ANALYSIS OF INCOME OF CITY GAS NETWORK ENTERPRISES - Коstiuk, V.; Коiuda, O.; Міlkin, І. (Municipal economy of cities. Series: «Economy science», 2022)
The article considers the method of calculating the influence of a number of factors on the change in income of enterprises of city gas networks. In the process of factor analysis of this indicator, it is recommended to use a number of economic-mathematical models containing factors that characterize the peculiarities of the production and operation process of enterprises of city gas networks. It is proposed to calculate the quantitative influence on the general change of this indicator of such important production and economic factors as the volume of natural gas obtained by the analyzed enterprise, the volume of gas supplied to the network, the volume of gas sold to consumers, the ratio of gas supply to the network, the sales ratio of gas to consumers, the average tariff of a unit of gas sold to consumers, the level of profitability of a unit of gas received, gas supplied to the network and gas sold to consumers. The positive aspect of this approach is that in the process of analytical calculations, indexes of factor indicators are used, and not their absolute values ​​for the case when such data are not available. At the same time, when using this method, it is suggested to follow the rule in which the basic value of the analyzed income indicator is multiplied by the indices of the previous factors of the calculation formula and by the relative growth of the factor whose influence is calculated. To determine the absolute impact of these factors on the overall change in income, it is recommended to carry out a step-by-step factor analysis of this indicator, which is based on the method of chain substitutions. This methodical approach allows, depending on the available initial information and the purpose of the analysis, to calculate the impact on the change in income of a different number of factors (two, three, etc.). The given method of modeling and factor analysis of income makes it possible to decompose this indicator into a number of constituent parts, to present it in the form of multiplicative economic and mathematical models, to determine the absolute and relative influence of the most important factors on the overall change of this indicator for any period of time of the enterprise’s operation, to investigate the regularities of such impact, use the obtained analytical information to substantiate organizational and management decisions regarding further improvement of the efficiency of use of available resources.